Hubungan antara Dukungan Keluarga dengan Resiliensi Penderita Tuberkulosis Paru - Fazriana, Erlina; Matrof, Randika Septembo; Daryaman, Usan; Sesilia, Fitri (PT Karya Inovasi Berkelanjutan, 2025)
Introduction and Methods Tuberculosis is a directly transmitted infectious disease caused by Mycobacterium tuberculosis. Pulmonary TB patients often exhibit signs and symptoms such as a productive cough lasting 2–3 weeks or more. In addition, they may experience psychological issues such as anxiety about infecting others, passive behavior, low self-esteem, and poor self-acceptance. This study aimed to analyze the relationship between family support and the resilience of pulmonary TB patients in the working area of Garuda Health Center, Bandung. The research used a correlational analytic method with a cross-sectional approach, involving 65 respondents selected through purposive sampling. Data collection instruments included the Multidimensional Scale of Perceived Social Support (MSPSS) questionnaire to assess family support and a resilience questionnaire for pulmonary TB patients. Data were analyzed bivariately using the Chi-Square test. Results The results showed that 46 respondents (70.8%) received good family support. A total of 38 respondents (58.5%) had high resilience levels. A statistically significant relationship was found between family support and the resilience of pulmonary TB patients at Garuda Health Center, Bandung, with a p-value of 0.000. Conclusion and Recommendation The study concluded that the higher the family support, the greater the resilience of TB patients. It is recommended that health professionals encourage families to provide consistent support to pulmonary TB patients. Contribution to the Sustainable Development Goals (SDGs) This study aimed to examine one of the contributing factors to the resilience of pulmonary TB patients, namely family support. The article contributes to the achievement of Sustainable Development Goal (SDG) 3: ensuring healthy lives and promoting well-being for all at all ages. Specifically, it aligns with Target 3.3, which aims to end the epidemics of AIDS, tuberculosis, malaria, and neglected tropical diseases by 2030, and combat hepatitis, water-borne diseases, and other communicable diseases.